Predictive factors for efficacy of oxaliplatin-based chemotherapy in advanced well-differentiated neuroendocrine tumors: an observational cohort study and meta-analysis - Wang, Jian; Wang, Xiangling; Chu, Yunxia; Li, Shuguang; Hao, Jing (Frontiers in Endocrinology, 2025)
BackgroundOxaliplatin-based chemotherapy (OX-CT) has shown promising antitumor activity in advanced well-differentiated neuroendocrine tumors (WD-NETs). However, no meta-analysis has been conducted to explore the factors associated with ORR and PFS of OX-CT, and data are still limited in Chinese cohort.MethodsWe performed a retrospective cohort study with advanced WD-NETs who received OX-CT. We also conducted a systematic review and performed a meta-analysis to explore factors associated with ORR and PFS.ResultsA total of 27 patients were included, with 21 receiving OX-CT as first line. Furthermore, 18 were of pancreas origin, and the median Ki-67 was 30%. The ORR and DCR were 29.6% and 81.5%, respectively. The median PFS was 9.3 months (95%CI: 4.6–14.0), and OS was not reached. A Ki-67 value >10% predicted higher ORR (36.4% vs. 0.0%, p = 0.28) and better PFS (10.0 vs. 2.1 months, p = 0.06). Patients with hepatic tumor burden ≤25% had a similar ORR (33.3% vs. 22.2%, p = 0.68), but with a trend of longer PFS (10.2 vs. 4.7 months, p = 0.21) than those >25%. Both ORR and PFS were independent of MGMT status. A total of 962 patients were included in the systemic review. The pooled ORR (28.2%, p = 0.84) and DCR (82.9%, p = 0.85) were comparable with this cohort. No difference was observed between GEMOX and FOLFOX/CAPOX in both ORR (23.9% vs. 29.6%, p = 0.19) and PFS (10.5 vs. 11.8 months, p = 0.69). Enhanced ORR was seen in pNETs than epNETs (36.8% vs. 16.7%, p < 0.001) and also in G3 NETs than G1–2 NETs (45.5% vs. 24.7%, p < 0.001). The pooled median PFS and OS were 10.8 months (95%CI: 8.8–12.8) and 30.4 months (95%CI: 24.8–35.9).ConclusionsOxaliplatin-based chemotherapy could be a good option for advanced WD-NETs with high Ki-67 index and pancreatic origin.